(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
Innovative aspects of preventive measures in legal education play an important role in developing legal awareness in students and preparing them for social responsibility. With the help of innovative approaches, modern technologies and methodologies are introduced into the educational process, and students acquire legal knowledge not only theoretically, but also practically. Through preventive measures, it is possible to form a legal culture, prevent violations, and effectively combat social problems